Leadership and culture in Knowledge Management: Islamic experience - Syed Nurulakla Syed Abdullah; Musa Abu Hassan (Universiti Sains Islam Malaysia, 2024)
A rich tapestry of Islamic scholarship and Islamic leadership intricately entwined with Islamic knowledge culture and Islamic knowledge management has never ceased to fascinate the present day Islamic educationists and researchers. One of the most distinguished features of Islamic education that has existed for the last fourteen centuries is free education in its purest meaning. The rich and the poor were provided with equal opportunity to acquire the highest order of Islamic knowledge. This profoundly beautiful Islamic culture has witnessed the emergence of some of the brightest intellectual luminaries of the Islamic world in the like of al-Ghazali, al-Biruni, al-Razi and al-Farabi. In a similar line of thought, the Islamic education of days gone by had seen the establishment of world renowned Islamic universities besides encouraging the love for books to the point of building a number of famous libraries for the collection of Islamic books and manuscripts.